Application of the National Osteoporosis Foundation Guidelines to Postmenopausal Women and Men: The Framingham Osteoporosis Study - Berry, Sarah D. (2010)
PURPOSE: Little is known about the public health impact of the National Osteoporosis Foundation (NOF) Guidelines. Therefore, we determined the proportion of U.S. Caucasians recommended for treatment of osteoporosis according to NOF Guidelines (2003 & 2008). METHODS: 1,946 postmenopausal women and 1,681 men ≥ age 50 years from the Framingham Study with information on BMD (1987-2001). Information on clinical predictors was used to estimate the 10-year probability of hip and major osteoporotic fracture by FRAX® (version 3.0). RESULTS: Overall proportion of women meeting treatment criterion was less when the 2008 NOF Guidelines were applied (41.1%) compared with 2003 Guidelines (47.8%). The proportion of women < age 65 years meeting treatment criterion was much less when applying 2008 Guidelines (23.1% in 2003, 8.3% in 2008), whereas the proportion of women > age 75 years increased slightly (78.3% in 2003, 86.0% in 2008). 17.0% of men ≥ age 50 years met treatment criterion (2.5% aged 50-64 years, 49.8% > age 75 years). CONCLUSIONS: Nearly one-half of Caucasian post-menopausal women and one-sixth of men aged 50 years and older would be recommended for osteoporosis treatment according to 2008 NOF Guidelines. Given the high proportion of persons recommended for treatment, NOF Guidelines may need to be re-evaluated with respect to budget impact.